2003
DOI: 10.1002/cncr.11629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on prognosis with imatinib mesylate therapy for patients with Philadelphia chromosome‐positive chronic myelogenous leukemia

Abstract: BACKGROUNDOlder age is a consistent poor prognostic factor in patients with Philadelphia chromosome (Ph)‐positive chronic myelogenous leukemia (CML). Whether this is related to an intrinsic worse disease biology or to inadequate drug delivery or excessive treatment‐associated toxicity is unknown. The availability of imatinib mesylate, a selective, Bcr‐Abl‐targeted therapy that is administered orally with minimal side effects, may clarify whether older age would remain an adverse factor (thus, implying a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 47 publications
3
43
0
2
Order By: Relevance
“…Interferon doses used to achieve response were lower in older patients, and adverse events were similar in both age groups. With the use of IM, older age appears to have lost much of its prognostic relevance, suggesting that the poor prognosis previously observed with older age was related to treatment-associated factors rather than to the biology of CML in older patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…Interferon doses used to achieve response were lower in older patients, and adverse events were similar in both age groups. With the use of IM, older age appears to have lost much of its prognostic relevance, suggesting that the poor prognosis previously observed with older age was related to treatment-associated factors rather than to the biology of CML in older patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…This improvement is especially notable in the younger patient populations, but there is reason to expect that improvement in survival will extend to older populations as further experience in the use of TKIs for CML is accumulated 24,25 and studies delineate the safest and most effective ways to use them in older patients. Relative survival for younger patients with CML who have survived for five years is greater than 90%, suggesting that late progression is becoming a rarer event in CML and that the course of the disease may be significantly delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients had a lower probability of CHR (53%) compared to younger ones (74%). Cortes et al 18 reported a higher probability of CHR (94%) in both groups of patients using the same criteria to define a CHR. The differences in CHR rates probably reflect a difference in the ability to assure high dose intensity between a single, very experienced center and a multi-institutional, national trial.…”
Section: -3mentioning
confidence: 94%
“…[8][9][10][11][12][13][14][15][16] Moreover, a major cytogenetic response is currently achieved in more than 80% of patients with early chronic phase disease and in more than 50% of those with late chronic phase disease. 17 In their series, Cortes et al 18 showed that imatinib eliminated the negative effect of age on response and survival. Within the frame of a large phase II trial of the GIMEMA CML Working Party, 19 which enrolled 284 late chronic phase patients treated with imatinib (400 mg daily) after interferon failure, we evaluated responses, progression-free and overall survival and compliance in patients younger and older than 65 years of age at enrollment.…”
Section: -3mentioning
confidence: 99%